Lowering dialysis sessions duration may be dangerous - Jacques Chanliau; Pierre-Yves Durand (RDPLF, 2021)
Dialysis session in less duration - either to give a better quality of life for the patient or to optimize the organization the dialysis institution - may have bad repercussions on the quality of the treatment and therefore the quality of life of the patient. According to the result of the publications listed in this work, we conclude that it is necessary to perform either longer sessions or more frequent treatments to limit the interval time between two sessions. As this is difficult to perform by the providers, we recommend to develop home dialysis to obtain the best result.